2014
DOI: 10.1200/jco.2012.47.6994
|View full text |Cite
|
Sign up to set email alerts
|

Single-Agent Rituximab for Primary CNS Lymphoma During Pregnancy As a Bridge to Definitive Management

Abstract: A 30-year-old female at 22 weeks gestation with her third child presented in February 2008 with a 10-day history of episodic imbalance with left-sided tonic-clonic activity without loss of consciousness. The episodes were followed by a progressive frontal headache. Initial exam was unremarkable, but a noncontrast magnetic resonance imaging (MRI) of the head demonstrated a large region of T2 hyperintensity in the white matter extending from the anterior right lateral ventricle to the right frontal lobe. A secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In recent years, a number of small studies or cases have been published that suggest use of the monoclonal antibody, rituximab, for the treatment of lymphoma or autoimmune disease is safe during pregnancy. 153 159 However, these same groups performed follow-up studies that identified the drug within the nasal cavity of newborns born to pregnant macaques treated during pregnancy. Therefore, this avenue of treatment may prove to be deleterious for the immune development during the first few months of life of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of small studies or cases have been published that suggest use of the monoclonal antibody, rituximab, for the treatment of lymphoma or autoimmune disease is safe during pregnancy. 153 159 However, these same groups performed follow-up studies that identified the drug within the nasal cavity of newborns born to pregnant macaques treated during pregnancy. Therefore, this avenue of treatment may prove to be deleterious for the immune development during the first few months of life of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Patients of PCNSL with administration of corticosteroid present with clinical improvement and regression which may be interpreted as a steroid-induced remission from an exacerbation of MS (4), often times, the white matter on neuroimaging studies shows abnormal signals in both PCNSL and MS, even brain biopsies may fail to detect tumor cells and show only demyelination because of different sites of sampling (5), radiographic improvement of PCNSL is not a consequence of restoring an impaired blood-brain barrier like MS, but is due to cytolytic effects of corticosteroid drugs on malignant lymphocytes (6). In some cases, repeated brain biopsy may, therefore, be necessary to provide.…”
Section: Discussionmentioning
confidence: 99%
“…This population of patients with autoimmune disease likely have baseline elevated risks during pregnancy due to disease related factors as well as receipt of other potentially teratogenic medications. While rituximab is not approved for use during pregnancy, there are case reports of successful treatment of lymphoma with rituximab in pregnant patients with good fetal outcomes and thus the lack of formal approval needs to weighed against the potential benefit particularly for aggressive B-cell NHLs [22, 23]. For newer targeted therapies including brentuximab vedotin and others, administration during pregnancy is not recommended given lack of fetus safety data for this therapy available to date.…”
Section: Therapymentioning
confidence: 99%